2010
DOI: 10.1002/acr.20344
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and incident hypertension: A systematic review and meta‐analysis

Abstract: Objective. A novel rodent model and a recent randomized trial of hyperuricemic adolescents with hypertension suggest a pathogenetic role of uric acid in hypertension, but it remains unknown whether these findings would be applicable to adult populations where the larger disease burden exists. We conducted a systematic review and meta-analysis to determine if hyperuricemia was associated with incident hypertension, particularly in various demographic subgroups. Methods. We searched major electronic databases us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
456
3
26

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 643 publications
(528 citation statements)
references
References 48 publications
27
456
3
26
Order By: Relevance
“…8 UA is closely associated with hypertension; a meta-analysis reported that higher UA was associated with a statistically significant elevation in incident hypertension. 17 In a recent prospective cohort study, we demonstrated that UA was associated with development of elevated blood pressure in overweight subjects. 10 Hypertension is also closely associated with DD, 5 both being implicated in the development of HFpEF.…”
Section: Hypertensionmentioning
confidence: 99%
“…8 UA is closely associated with hypertension; a meta-analysis reported that higher UA was associated with a statistically significant elevation in incident hypertension. 17 In a recent prospective cohort study, we demonstrated that UA was associated with development of elevated blood pressure in overweight subjects. 10 Hypertension is also closely associated with DD, 5 both being implicated in the development of HFpEF.…”
Section: Hypertensionmentioning
confidence: 99%
“…SUA was also found to predict new-onset hypertension in a Japanese general population 12 , and a recent meta-analysis had found similar data 13 .…”
Section: Prognostic Effect Of Uric Acidmentioning
confidence: 76%
“…Asimismo, los niños con elevación de la presión arterial presentan niveles altos de ácido úrico comparado con niños normotensos 23 , lo cual estaría asociado a un elevado riesgo (~2 veces) de hipertensión en la adolescencia 24 . Para complementar, en adultos y sobre todo en mujeres, se ha reportado que la elevación en los niveles de ácido úrico constituye un factor de riesgo independiente para hipertensión 25 o muerte por enfermedad coronaria 26 . Cabe resaltar, que no se ha estudiado la relación entre el ácido úrico al nacimiento y el riesgo de hipertensión del embarazo en la vida adulta.…”
Section: áCido úRico Y Pre-eclampsiaunclassified